2010
DOI: 10.1111/j.1365-2095.2010.00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary arginine requirement of Heteropneustes fossilis fry (Bloch) based on growth, nutrient retention and haematological parameters

Abstract: Dietary arginine requirement of Heteropneustes fossilis fry (3.0 ± 0.5 cm; 5.1 ± 0.3 g) was determined by feeding casein‐gelatin‐based isonitrogenous (400 g kg−1 crude protein) and isocaloric (17.97 kJ g−1) amino acid test diets containing graded levels of l‐arginine (15, 17, 19, 21, 23 and 25 g kg−1 dry diet) for 12 weeks. Maximum absolute weight gain (AWG) (44.4), best feed conversion ratio (FCR) (1.22), highest protein retention efficiency (PRE%) (41%), energy retention efficiency (ERE%) (75%), best conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 77 publications
(112 reference statements)
7
46
1
Order By: Relevance
“…A similar tendency to that of whole-body was observed for muscle composition but protein content was not significantly different among treatments. These results are in agreement with previous studies on Indian major carp (Ahmed and Khan, 2004), black sea bream (Zhou et al, 2010) and H. fossilis (Khan and Abidi, 2011). Arginine is one of the most versatile amino acids and is a crucial precursor for protein synthesis (Wu and Morris, 1998).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A similar tendency to that of whole-body was observed for muscle composition but protein content was not significantly different among treatments. These results are in agreement with previous studies on Indian major carp (Ahmed and Khan, 2004), black sea bream (Zhou et al, 2010) and H. fossilis (Khan and Abidi, 2011). Arginine is one of the most versatile amino acids and is a crucial precursor for protein synthesis (Wu and Morris, 1998).…”
Section: Discussionsupporting
confidence: 94%
“…Analysis of hematological parameters provides valuable information on metabolic disorders, deficiencies and chronic stress status (Bahmani et al, 2001). Previous studies showed the changes in blood components in response to dietary supplementation of EAAs (Huai et al, 2009;Khan and Abidi, 2011;Zhou et al, 2010). Also, our previous study exhibited the significant effect of dietary valine on red sea bream hematology (Rahimnejad and Lee, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…The whole-body protein of H. fossilis fry increased with dietary protein and correlated negatively with body moisture. Similar findings have been reported for other fish species (Hidalgo et al 1993;Khan & Abidi 2011). Moisture content showed an inverse relationship with carcass lipid when dietary protein level was increased.…”
Section: Resultssupporting
confidence: 77%
“…African catfish C. gariepinus is a globally popular aquaculture species largely distributed throughout Africa and Asia [2,[14][15][16][17][18]. It is widely cultured in freshwater ponds because of their easiness in reproduction, high growth rate, tolerance to high densities culture conditions, resistance to diseases, excellent flesh quality and ability to accept a wide variety of feed [15][16][17]19].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely cultured in freshwater ponds because of their easiness in reproduction, high growth rate, tolerance to high densities culture conditions, resistance to diseases, excellent flesh quality and ability to accept a wide variety of feed [15][16][17]19]. The technics culture for the full life cycle of African catfish has been well-established and the global production of this species has been increased from 11.8 tons in 2000 to 517.4 tons in 2010 [20].…”
Section: Introductionmentioning
confidence: 99%